When do emergencies happen? Exploring circadian, weekly, and seasonal trends in ambulance calls in Cyprus - Protopapas, Andreas; Mamais, Ioannis; Constantinou, Riana; Iordanou, Stelios; Prodromou, Maria; Mappouras, Stelios; Kyriacou, Efthyvoulos C. (My University, 2025)
The demand for ambulances has steadily risen over the past few decades, straining Emergency Medical Services (EMS) and emergency departments (EDs). Understanding the temporal patterns of emergency calls can improve ED patient flow. The aim of this study was to analyze the overall demand for emergency ambulance calls in Cyprus focusing on call reasons, time of day, day of the week, and year season.
Keywords: Ambulance services; Circadian rhythm; Emergency medical dispatch; Emergency medical services; Health services planning